Evaluating ChatGPT’s Mandarin “yue” pronunciation system in language learning - Lau, Yoke Lian; Tan, Swee Mee; Abu Bakar, Anna Lynn; Yong, Zi Xian; Yong, Zi Hong; Nasir, Ernahwatikah; Jung Ku, Chen (IAES International Journal of Artificial Intelligence (IJ-AI), 2025)
By incorporating voice control technology into ChatGPT, it becomes possible to engage in conversations or dialogues with individuals who are actively engaged in the process of acquiring language skills. Our study team conducted a modest experiment to evaluate the efficacy of a voice control feedback system in facilitating the mastery of the most challenging pronunciation of the Mandarin syllable "yue". The objective of this study is to evaluate the effectiveness of voice-controlled ChatGPT in aiding learners to acquire accurate pronunciation of the Mandarin phoneme "yue". Furthermore, the study seeks to investigate the methods utilised by the ChatGPT model in identifying and distinguishing the word "yue" when it is used alone or in combination with "ye" and "yi". We employed many testing approaches, including single-word instances, paired instances, and the integration of phrases. In addition, we evaluated the model's ability to accurately detect the term "yue" in short sentences and, ultimately, in a longer sentence.